2003
DOI: 10.1523/jneurosci.23-27-09004.2003
|View full text |Cite
|
Sign up to set email alerts
|

Human α4β2 Acetylcholine Receptors Formed from Linked Subunits

Abstract: We prepared concatamers of alpha4 and beta2 subunits for human nicotinic acetylcholine receptors (AChRs), in which the C terminus of alpha4 was linked to the N terminus of beta2, or vice versa, via a tripeptide sequence repeated 6 or 12 times, and expressed them in Xenopus oocytes. Linkage did not substantially alter channel amplitude or channel open-duration. Linkage at the C terminus of alpha4 prevented AChR potentiation by 17-beta-estradiol by disruption of its binding site. Assembly of AChRs from concatame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
190
1
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 160 publications
(211 citation statements)
references
References 35 publications
16
190
1
3
Order By: Relevance
“…A potential hazard of subunit concatenation is the possibility that not all subunits in the concatemer will participate in the formation of the complex, leading to erroneous results. For example, either ␣ 4 -␤ 2 or ␤ 2 -␣ 4 nicotinic acetylcholine receptor subunit dimers were unexpectedly found to form functional receptors (34). It was shown that dimers could be incorporated into two separate pentamers, leading to a receptor dimer held together by the linker.…”
Section: Discussionmentioning
confidence: 99%
“…A potential hazard of subunit concatenation is the possibility that not all subunits in the concatemer will participate in the formation of the complex, leading to erroneous results. For example, either ␣ 4 -␤ 2 or ␤ 2 -␣ 4 nicotinic acetylcholine receptor subunit dimers were unexpectedly found to form functional receptors (34). It was shown that dimers could be incorporated into two separate pentamers, leading to a receptor dimer held together by the linker.…”
Section: Discussionmentioning
confidence: 99%
“…3E). These residues likely contribute to αβ and ββ interfaces in α4β2 nAChRs (21,28,29). In the human β2 subunit, these residues on the complementary face of the binding site correspond to V111, F119, and L121 (loop E) and W57 (loop D).…”
Section: Structure-guided Mutagenesis Analysis Of Varenicline Interacmentioning
confidence: 99%
“…Given that α5 gene deletion did not change cytisine-sensitive [ 3 H]-epibatidine binding (Figure 3), we suspect that both α4β2 and α4α5β2 nAChRs are normally expressed in striatal dopaminergic nerve terminals and that α4β2 nAChRs replace the α4α5β2 nAChRs in the α5 null mutant mice. It has been repeatedly demonstrated that α4β2 nAChRs expressed in Xenopus oocytes or cultured cells can assemble in two stoichiometric forms with differing sensitivities to activation by agonists [108,109,110]. In neurons there is evidence for two forms of α4β2 receptors with functional differences [111, and MJ Marks, unpublished data); however, these two forms may have similar binding affinities (MJ Marks, unpublished data).…”
mentioning
confidence: 99%